A structural, genetic and clinical comparison of CAR-T cells and CAR-NK cells: companions or competitors? - Andrea, Alain E.; Chiron, Andrada; Sarrabayrouse, Guillaume; Bessoles, Stéphanie; Hacein-Bey-Abina, Salima (Frontiers in Immunology, 2024)
In recent years, following the groundbreaking achievements of chimeric antigen receptor (CAR) T cell therapy in hematological cancers, and advancements in cell engineering technologies, the exploration of other immune cells has garnered significant attention. CAR tCAR-Therapy extended beyond T cells to include CAR natural killer (NK) cells and CAR-macrophages, which are firmly established in the clinical trial landscape. Less conventional immune cells are also making their way into the scene, such as CAR mucosal-associated invariant T (MAIT) cells. This progress is advancing precision medicine and facilitating the development of ready-touse biological treatments. However, in view of the unique features of natural killer cells, adoptive NK cell immunotherapy has emerged as a universal, allogenic, "off-the shelf" therapeutic strategy. CAR NKCAR-NK cytotoxic cells present targeted tumor specificity but seem to be devoid of the side effects associated with CAR TCAR-T cells. CAR NKCAR-NK cells appear to be potentially promising candidates for cancer immunotherapy. However, their application is hindered by significant challenges, particularly the limited persistence of CAR NKCAR-NK cells in the body, which poses a hurdle to their sustained effectiveness in treating cancer. Based upon the foregoing, this review discusses the current status and applications of both CAR TCAR-T cells and CAR NKCAR-NK cells in hematological cancers, and provides a comparative analysis of the structure, genetics, and clinical outcomes between these two types of genetically modified immune cells.